GIS-based flood risk management plan an approach to disaster risk reduction in barangay Hinaplanon, Iligan city, Philippines. - Albiento, Elizabeth Edan M. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
Climate change has exacerbated frequent and intense flooding in barangay Hinaplanon in Iligan city as the years passed. It is for this reason that a GIS-based flood risk management plan is presented to reduce the risks and minimize the effects of possible disasters due to flooding. Household geographic and demographic data including buildings stocks were gathered to develop a social vulnerability map overlaid to the flood hazard scenario maps. These were processed using QGIS to facilitate te identification of high-risk areas on a per purok level. Results from the household social vulnerability assessment showed that the Bayug island has the highest number of highly vulnerable households while those in phase 3 and 5 bahayan buroks were identified high-risk puroks for 25 Year Return Period (YRP) and 50 YRP. The flood risk mapfor 100 YRP identified four puroks as high-risk puroks. All the generated thematic maps were integrated into the flood risk management plan to aid the barangay officials in planning, managing, deciding and executing plans in flooding events.